Assessing patient safety in Canadian ambulatory surgery facilities: A national survey. Issue 1 (March 2014) - Ahmad, Jamil; Ho, Olivia A; Carman, Wayne W; Thoma, Achilles; Lalonde, Donald H; Lista, Frank
Background: There has been increased interest regarding patient safety and standards of care in Canadian ambulatory surgery facilities where surgical procedures are performed. The Canadian Association for Accreditation of Ambulatory Surgical Facilities (CAAASF) is a national organization formed to establish and maintain standards to ensure that surgical procedures conducted outside of public hospitals are performed safely. Objective: To determine how many procedures are performed annually at CAAASF member sites, and to examine complication rates and several key patient safety practices. Methods: All 69 facilities accredited by the CAAASF were surveyed. The survey focused on procedural data, complication rates and patient safety interventions. Results: In 2010, 40, 240 estimated procedures were performed. A total of 263 (0.007%) complications were reported. Sixteen (0.0004%) patients required reoperations in hospital and 19 (0.0004%) patients required transfer to hospital on the day of surgery. There were only two mortalities within 30 days of surgery reported in the past five years. With regard to patient safety practices, 93% used antimicrobial prophylaxis, 100% used strategies to maintain normothermia and 82% used measures for venous thromboembolism prevention. Conclusion: The present study is the first to report on the Canadian experience in ambulatory surgery facilities and provides insight into current practices at these facilities. Appropriate accreditation of ambulatory surgery facilities, well-established patient safety-related standards of care, careful patient selection and procedures performed by qualified health care professionals with appropriate certification practicing within the scope of their practice form the basis for safe and effective ambulatory surgery.